Analisis Putusan Perbuatan Melawan Hukum Perkara Nomor: 359/Pdt.G/2024/PN Jkt.Brt - Firial Tiara Efriliani; Risa Dewi Oktaviani; Sulastri S (Media Hukum Indonesia (MHI), 2026)
This study discusses how the principles of contract law are applied in civil disputes in Decision Number 359/Pdt.G/2024/PN West Jakarta. The conflict arose from a lease agreement between PT. Tropic World Paradise and Liauw Reolita, when the absence of a building permit (IMB/PBG) was considered to be hindering the tenant's business. A lawsuit was then filed based on Article 1365 of the Civil Code, involving the notary who drafted the lease agreement. The results of the study show that the allegation of unlawful acts was not proven. The judge ruled that the plaintiff had been aware of the condition of the building from the outset, that the agreement was valid, and that the notary had performed his duties in accordance with his authority. Conversely, the plaintiff was found to have committed an unlawful act by continuing to occupy the building after the lease period had ended. Finally, the lawsuit was dismissed and the counterclaim was granted. This finding emphasizes the importance of good faith, legal certainty, and clear evidence in determining the responsibilities of the parties in a lease agreement.